Delving into learner autonomy in an EFL MOOC in China: a case study. Issue 3 (4th March 2022) - Ding, Yan; Shen, Huizhong
Abstract: Autonomy of language learners in technology-supported learning environments has attracted much scholarly attention. However, few studies, to date, have examined the issue in the emerging context of language MOOCs. The present study complemented this line of research via a qualitative investigation of a group of Chinese EFL learners in an English language MOOC. Data were collected via a prior interview ( N =  38), four interviews held at different stages of the MOOC ( N =  36, 27, 17, 13, respectively), and a post-course interview for dropouts ( N =  14). A framework consisting of seven constructs in three dimensions, namely, the situational, the behavioral, and the psychological, was employed for analyzing the data. The results showed that the learners exhibited individual and dimensional variation in the extent to which they exercised autonomy. Participants were also observed to have adopted a variety of metacognitive strategies, motivation control strategies, and emotion control strategies to regulate their learning. The findings highlight the complexity of learner autonomy as displayed in the new learning interface as well as the potential of language MOOCs for fostering learner autonomy.